One-Dimensional Nanostructured TiO2 for Photocatalytic Degradation of Organic Pollutants in Wastewater - Ting Feng; Gen Sheng Feng; Lei Yan; Jia Hong Pan (International Journal of Photoenergy)
The present paper reviews the progress in the synthesis of one-dimensional (1D) TiO2 nanostructures and their environmental applications in the removal of organic pollutants. According to the shape, 1D TiO2 nanostructures can be divided into nanorods, nanotubes, nanowires/nanofibers, and nanobelts. Each of them can be synthesized via different technologies, such as sol-gel template method, chemical vapor deposition, and hydrothermal method. These methods are discussed in this paper, and the recent development of the synthesis technologies is also presented. Furthermore, the organic pollutants, degradation using the synthesized 1D TiO2 nanostructures is studied as an important application of photocatalytic oxidation (PCO). The 1D nanostructured TiO2 exhibited excellent photocatalytic activity in a PCO process, and the mechanism of photocatalytic degradation of organic pollutants is also discussed. Moreover, the modification of 1D TiO2 nanostructures using metal ions, metal oxide, or inorganic element can further enhance the photocatalytic activity of the photocatalyst. This phenomenon can be explained by the suppression of e−-h+ pairs recombination rate, increased specific surface area, and reduction of band gap. In addition, 1D nanostructured TiO2 can be further constructed as a film or membrane, which may extend its practical applications.